DEVELOPMENT AND VALIDATION OF A TOOL TO FACILITATE RESILIENCE AND GOOD MENTAL HEALTH: THE MY SEJAHTERA ECOLOGY MAP - MOHD NAZORI, MOHD NAZIR; SAAD, NURULWAHIDA; IBRAHIM, MUHAMAD ARIFF; SAMSUDDIN, NIZA; AHMAD DHANI, MAR’AIN (International Journal of Allied Health Sciences, 2025)
Background: There has been a growing body of research on the influence of social environment on mental wellbeing. Bronfenbrenner’s Ecology Systems theory has proposed an extensive description of components and relationships of the social ecology of a person for their growth. However, there is a paucity of tools available for mental health professionals in implementing the theory within their practice. Therefore, this study aimed to develop and validate a tool to explore the social ecology of a person to aid understanding the influence of social ecology on the state of mental wellbeing. Methods: This study developed instructions to draw and explore social ecology and established several validity evidences. Content validity used item-related content validity index employing five experts in psychiatry, psychology, and counselling to review the instructions for the tool. Face validity was established using face validity index among ten working adults. Finally, criterion-related validity was established by improvement in mental health self-efficacy measured using Mental Health Confidence Scale among 41 working adults. Descriptive analysis used frequency and percentage for categorical variables, and mean and standard deviation for numerical variables. Inferential analysis used paired-sample t-test analysed on SPSS 29. Results: The My Sejahtera Ecology Map (MySEM) tool showed good content and face validity indices ranging from 0.80 to 1.00. Mental health self-efficacy showed significant improvement in optimism (p < 0.05) and factor coping (p < 0.001) after the MySEM activity. Conclusion: The tool has promising benefits in improving mental health self-efficacy through increasing factor-coping and optimism. The MySEM tool provided a standardized approach to apply the Bronfenbrenner’s Ecology Systems theory for use by mental health professionals.